2010
DOI: 10.14210/bjast.v13n2.p59-66
|View full text |Cite
|
Sign up to set email alerts
|

Bioacumulação de metais pesados em moluscos bivalves: aspectos evolutivos e ecológicos a serem considerados para a biomonitoração de ambientes marinhos

Abstract: The knowledge on the contaminants agents' bioaccumulation dynamic in bivalve tissues is important because shell fish consumption may represent a toxic risk to humans. By looking at the selective pressure to which the bivalve mollusks were submitted along their evolutionary process, a better understanding on bivalves as a biologic model for environmental contamination assessments can be achieved. The capacity to control toxic elements by bivalves is especially important to environment toxicology. Bivalves that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
11

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 32 publications
0
6
0
11
Order By: Relevance
“…Specifically for Zn, the highest concentration in the summer could be related not only to the higher rainfall of this period, but also to reproduction (Casarini et al, 2010), since reproductive peaks were identified in January (Galvão et al, 2009). For the Mytilus edulis mussel, higher concentrations of Zn were observed in the spawning stage, which is attributed to the synthesis of a group of proteins, such as metallothioneins that are responsible for the preferential accumulation of some metals (Carvalho et al, 2001).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Specifically for Zn, the highest concentration in the summer could be related not only to the higher rainfall of this period, but also to reproduction (Casarini et al, 2010), since reproductive peaks were identified in January (Galvão et al, 2009). For the Mytilus edulis mussel, higher concentrations of Zn were observed in the spawning stage, which is attributed to the synthesis of a group of proteins, such as metallothioneins that are responsible for the preferential accumulation of some metals (Carvalho et al, 2001).…”
Section: Resultsmentioning
confidence: 97%
“…Bivalve mollusks, such as mussels, are known for their ability to concentrate trace elements (Resgalla Jr. et al, 2008;Wallner-Kersanach & Bianchini, 2008); these animals can accumulate cadmium concentrations up to 100 thousand times higher than the ones observed in the waters where they live (Galvão et al, 2009). The retention and absorption of lead in the digestive tract of mollusks are linked to several factors that should be considered, such as salinity, hygroscopicity, concentration, larval phase, respiratory rate, and duration of exposure (Barbieri, 2009a(Barbieri, , 2009bBarros & Barbieri, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Determinar as concentrações dos contaminantes nos organismos marinhos proporciona o conhecimento da biodisponibilidade dos metais traço nos diferentes ecossistemas, o que permite avaliar os riscos potenciais aos quais a população está exposta, principalmente através da alimentação (GALVÃO et al, 2009). Portanto, o objetivo deste estudo foi traçar um perfil do grau de contaminação por metais traço em mexilhões Perna perna em diferentes sistemas aquáticos na costa sul e sudeste brasileira através da revisão de literatura.…”
Section: Introductionunclassified
“…Para estudar, qualitativamente e quantitativamente, os contaminantes de um organismo considerado um bom biomonitor, no escopo da poluição de zonas costeiras, é necessário testar esses organismos de modo que atendam algumas características, dentre elas: (RAINBOW, 2006;GALVÃO et al, 2009;TEIXEIRA, 2012) • Ser sésseis, de modo que qualquer evento de entrada de contaminantes no ambiente faça com que esses organismos sejam afetados e esses contaminantes sejam incorporados, de alguma forma;…”
Section: Biomonitoramento E Diagnóstico Ambientalunclassified
“…Entre os organismos utilizados mundialmente, os bivalves têm se destacado em diversos estudos (YUSOF et al, 2004;GALVÃO et al, 2009;. Entretanto, vários estudos incluem outros organismos como biomonitores do ambiente marinho, como algas (CONTI e CECCHETTI, 2003;ZBIKOWSKI et al, 2007;MAJER et al, 2014), e ouriços (MAJER et al, 2014;ALVES et al, 2017).…”
Section: Biomonitoramento E Diagnóstico Ambientalunclassified